MECHANICAL PROPERTIES AND MICROSTRUCTURES OF REGENERATED CEMENT FROM WASTE CONCRETE - YILENG DU; HONGJUAN ZUO (Journal of Engineering Studies and Research)
It has been a long time since humans started using waste materials in engineering applications. This approach not only reduces the yield of waste, while minimizing the costs of disposal but also limit the cost of new materials. In the field of construction, the reuse of waste concretes has been a strong research in recent years. However the processing of the wastes normally involves complicated processing and lab equipment. In this report we crush and dehydrate waste concretes with normal lab facilities and re-make the cement composites. The waste concretes were crushed and dehydrated at two temperatures, 1280 and 1400 ˚C. To balance the concentration of silica and lime, extra lime at 28.5 % and 16 % were added to the waste concretes. The resultant materials were evaluated with respect to the chemical composition, mechanical properties, and microstructures. It is concluded that the material dehydrated at 1400 ˚C and containing 28.5 % lime presents the best mechanical performance. This report presents a simple and inexpensive method to reuse the waste concretes in applications such as pavements.